2010
DOI: 10.1016/j.neulet.2010.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Potent neuroprotective effects of novel structural derivatives of valproic acid: Potential roles of HDAC inhibition and HSP70 induction

Abstract: Emerging evidence suggests that the neuroprotective effects of valproic acid (VPA) occur via inhibition of histone deacetylases (HDACs) and activation of gene expression. This study assessed the ability of four VPA derivatives to cause histone hyperacetylation and protect against glutamate-induced excitotoxicity in cultured neurons. We found that (S)-2-pentyl-4-pentynoic acid (compound III) and (±)-2-hexyl-4-pentynoic acid (compound V) were far more potent and robust than VPA in inducing histone hyperacetylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Our previous study found that HSP70 is an important target for VPA and other HDAC inhibitors, and is part of the mechanism through which they exert neuroprotective effects against glutamate-induced excitotoxicity in primary neuronal cultures (Marinova et al, 2009; Leng et al, 2010), as well as in a rat model of cerebral ischemia (Ren et al, 2004; Kim et al, 2007a). HSP70 upregulation has been shown to stabilize the NF-κB-IκB complex, thereby preventing the nuclear translocation of the activated NF-κB subunits (Rel A and p50) to elicit inflammatory responses (Zheng et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that HSP70 is an important target for VPA and other HDAC inhibitors, and is part of the mechanism through which they exert neuroprotective effects against glutamate-induced excitotoxicity in primary neuronal cultures (Marinova et al, 2009; Leng et al, 2010), as well as in a rat model of cerebral ischemia (Ren et al, 2004; Kim et al, 2007a). HSP70 upregulation has been shown to stabilize the NF-κB-IκB complex, thereby preventing the nuclear translocation of the activated NF-κB subunits (Rel A and p50) to elicit inflammatory responses (Zheng et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many in vitro and in vivo studies have shown that HDIs protect against a range of toxic insults through the modulation of histones [38], increased the transcription of free radical scavengers [39,40], heat shock proteins [41][42][43] and anti-apoptotic Bcl-2 family members [39,44] as well as decreasing the expression of inflammatory mediators [38,45,46], reducing excitotoxicity [47,48], oxidative stress [49,50] and enhancing neurotrophic factor expression [51]. As many of these events have been implicated in mediating or protecting against dopaminergic cell death in PD, HDIs are appealing candidates for promoting dopaminergic neuronal survival in PD [21,52].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, beta-hydroxybutyate, an endogenous and specific inhibitor of class I HDACs (Shimazu et al, 2012), has been reported to protect primary rat mesencephalic neurons from 1-methyl-4-phenylpyridinium [MPP(+)]-induced toxicity (Kashiwaya et al, 2000). Another study reported regulation of heat shock protein 70 (Hsp70) expression through changes to the di-and trimethylation of histone H3 lysine 4 (H3K4me2 and H3K4me3) and p300 (HAT) recruitment (Marinova et al, 2009;Marinova et al, 2011;Leng et al, 2010). As a member of the heat shock protein family, Hsp70 is involved in protein folding, is able to upregulate the apoptotic regulator Bcl2, and is involved in several additional anti-apoptotic mechanisms (Yenari et al, 2005).…”
mentioning
confidence: 99%